Al-Hajjaj's Strategies in Surat Al-Rum: A Linguistic Argumentative Study in The Holy Qur'an - Nadia Lotfy Nasser (Universitas Ahmad Dahlan, 2023)
The Holy Surah included dialectical methods, such as the argumentative strategy that achieves persuasion through linguistic mechanisms and the argumentative ladder, according to Oswald Decro's theory of linguistic arguments. The importance of this research is that it sheds light on the ability of the linguistic mechanisms in Surat Al-Rum to achieve the argumentative function and influence the recipient. The main question of the research is whether the linguistic and rhetorical mechanisms and the argumentative scale achieved the argumentative function and affected the recipient? The approach that the research follows is descriptive and analytical, as it follows the approach of the linguistic arguments’ theory of